Risk provision using field spectroscopy to identify spectral regions for the detection of defects in flexible pavements - Mettas, Christodoulos; Agapiou, Athos; Themistocleous, Kyriacos; Neocleous, Kyriacos; Hadjimitsis, Diofantos G.; Michaelides, Silas (My University, 2016)
Natural and physical hazards accelerate the deterioration of asphalted surfaces. Climatic factors are unavoidable and can affect the properties of asphalt mixtures, making them weaker and less durable. Thus, continuous monitoring of bituminous surfaces is something that can reduce the risks of public health. Remote sensing techniques have become an effective, noninvasive method for early detection of damaged asphalt pavements. This paper outlines a range of different remote sensing methodologies that can be used to monitor asphalt road pavements. This is complemented by the use of field spectroscopy for the examination of asphalt pavements of varying age and conditions. The results of the study found spectral differences regarding asphalt defects, such as physical cracking, patched cracking and polishing. These spectral changes were examined through “in-band” simulation analysis of the Landsat 7 ETM+ sensor, using appropriate relative spectral response filters, concluding that the ratio band 5/band 1 can be used to distinguish asphalt pavements of different date of construction and condition.
Keywords: Aging; Asphalt pavements; Cyprus; Pavement defects; Remote sensing; Spectral signatures